Hypnosis in palliative care: from clinical insights to the science of self-regulation - Landry, Mathieu; Stendel, Moriah; Landry, Michel; Raz, Amir (Annals of Palliative Medicine, 2018)
Palliative care spans a wide-ranging spectrum: from pain-management to spiritual support. As the demand for end-of-life care increases, so does the demand for innovative, effective, interventions. Mind-body techniques seem especially advantageous in a palliative context. Here we show that hypnosis serves an excellent adjunct therapy in palliative care to boost the efficacy of standard treatments. With the overarching goal of bridging clinical and scientific insights, we outline how five core principles of hypnosis can benefit the diverse needs of palliative care.